Evaluation of Influenza Vaccine Effectiveness and Effective Factors of Accepting Vaccine Injection among Health Care Workers in Alzahra Hospital, Isfahan, Iran, 2018 - Anahita Babak; Mohamad Reza Abdollahzadeh; Manizhe Shams; Alireza Safaeian (مجله دانشکده پزشکی اصفهان, 2020)
Background: Regarding the increasing importance of influenza, especially in those at risk, this study aimed to explore the effectiveness and the effective factors of influenza vaccination acceptance among the staff of Alzahra hospital, Isfahan, Iran